Pengaruh Media Sosial dan Lingkungan Keluarga Terhadap Keputusan Investasi Mahasiswa - Wau, Febi Nur Afni; Ade Prabowo, Bayu (Universitas Pamulang, 2026)
This study examines the influence of social media and family environment on investment decisions of STIEPARI students in Bawen. Using a quantitative approach with multiple linear regression analysis on 85 respondents, this research reveals that both social media (β=0.259, p=0.004) and family environment (β=0.426, p=0.000) have positive and significant effects on investment decisions, both partially and simultaneously. Family environment demonstrates more dominant influence compared to social media, indicating that in Indonesia's collectivist culture, traditional family influence remains central even in the digital era. The model explains 85.5% of the variation in investment decisions (R²=0.855). These findings enrich behavioral finance literature by demonstrating a unique Indonesian pattern integrating modern social media influences with traditional family values. Practical implications emphasize the importance of holistic approaches in designing financial literacy programs involving both social media platforms and family participation.